EDUKASI KEPADA MASYARAKAT TENTANG PROSES PEMBUATAN CHICKEN CHEESE BALL DAN STRATEGI PEMASARANNYA - Aulia Ayu; Naswa Mar’atus; Shella Wulandari; Mellyana Herawati; Cantika Ratna Wati; Unna Ria Safitri (KRIDA CENDEKIA, 2025)
This community service activity aims to enhance the knowledge and skills of the residents of Kedung Mulyo Village RT 05/RW 04, Kemusu District, Boyolali Regency, in processing chicken meat into the innovative product chicken cheese ball and introducing digital marketing strategies. The methods employed include presentations, hands-on product demonstrations, and digital marketing training using platforms such as Instagram, Facebook, WhatsApp, and TikTok. The results show that the community gained new insights into the production process of nutritious chicken cheese balls, which have the potential to become micro-enterprises based on local food resources. Furthermore, digital marketing training improved the community’s literacy and motivation to utilize social media as an effective and broader promotional tool. This activity is expected to lay the foundation for micro-business development, promote food self-sufficiency, and improve the welfare of the village community